Sex hormones, intestinal inflammation, and the gut microbiome: Major influencers of the sexual dimorphisms in obesity - Brettle, Holly; Tran, Vivian; Drummond, Grant R.; Franks, Ashley E.; Petrovski, Steve; Vinh, Antony; Jelinic, Maria (Frontiers in Immunology, 2022)
Obesity is defined as the excessive accumulation of body fat and is associated with an increased risk of developing major health problems such as cardiovascular disease, diabetes and stroke. There are clear sexual dimorphisms in the epidemiology, pathophysiology and sequelae of obesity and its accompanying metabolic disorders, with females often better protected compared to males. This protection has predominantly been attributed to the female sex hormone estrogen and differences in fat distribution. More recently, the sexual dimorphisms of obesity have also been attributed to the differences in the composition and function of the gut microbiota, and the intestinal immune system. This review will comprehensively summarize the pre-clinical and clinical evidence for these sexual dimorphisms and discuss the interplay between sex hormones, intestinal inflammation and the gut microbiome in obesity. Major gaps and limitations of this rapidly growing area of research will also be highlighted in this review.